2010
DOI: 10.1371/journal.pone.0012348
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Root Transcriptome Remodeling of Arabidopsis in Response to Mars-Like Levels of Magnesium Sulfate

Abstract: BackgroundMartian regolith (unconsolidated surface material) is a potential medium for plant growth in bioregenerative life support systems during manned missions on Mars. However, hydrated magnesium sulfate mineral levels in the regolith of Mars can reach as high as 10 wt%, and would be expected to be highly inhibitory to plant growth.Methodology and Principal FindingsDisabling ion transporters AtMRS2-10 and AtSULTR1;2, which are plasma membrane localized in peripheral root cells, is not an effective way to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 38 publications
(46 reference statements)
1
41
1
Order By: Relevance
“…It was found that atmgt1 plants had almost similar biomass and leaf chlorophyll content with wild types under high Mg 2C stress (MgT) but the expression levels of AtMGT1, AtMGT7 and AtMHX were up-regulated in the wild type though non-significantly. 10 Although little change in the expression levels of these MgTRs were observed in microarray analysis when the plants were under MgSs, [8][9][10] results obtained from real time PCR detection showed significant changes for many MgTRs, for example AtMGT6 responding to Mg starvation. 30 We recently found that 8 AtMGTs and AtMHX were responding to MgT 1 and the findings were consistent with results obtained from serpentine conditions, where 6 MgTRs were highly expressed in the mesophyll and some could be correlated with higher accumulation of Mg in plants.…”
Section: Magnesium Transporters In Plants Responding To Magnesium Strmentioning
confidence: 97%
See 4 more Smart Citations
“…It was found that atmgt1 plants had almost similar biomass and leaf chlorophyll content with wild types under high Mg 2C stress (MgT) but the expression levels of AtMGT1, AtMGT7 and AtMHX were up-regulated in the wild type though non-significantly. 10 Although little change in the expression levels of these MgTRs were observed in microarray analysis when the plants were under MgSs, [8][9][10] results obtained from real time PCR detection showed significant changes for many MgTRs, for example AtMGT6 responding to Mg starvation. 30 We recently found that 8 AtMGTs and AtMHX were responding to MgT 1 and the findings were consistent with results obtained from serpentine conditions, where 6 MgTRs were highly expressed in the mesophyll and some could be correlated with higher accumulation of Mg in plants.…”
Section: Magnesium Transporters In Plants Responding To Magnesium Strmentioning
confidence: 97%
“…1,4,8 MgSs markedly inhibit plant growth, resulting in shorter roots, smaller shoots, and necrotic spots. 1,4,9,10,15,17,18 Hermans et al 4,8 found that MgD reduced the growth of young leaves more than the roots, but our results indicated that both root and leaf were severely inhibited by MgD (Fig. 1B) In addition to carbon fixation in photosynthesis, magnesium also acts as activator or cofactor of enzymes in carbohydrate metabolism, e.g., fructose-1,6-bisphosphatase (FBPase), glutamate synthetase, UDP-D-, ADP-D-, and GDPD-glucose pyrophosphorylase, and UDP-D-glucuronic acid pyrophosphorylase.…”
Section: Morphogenesis Remodeling Of Plants By Magnesium Stressesmentioning
confidence: 99%
See 3 more Smart Citations